Política educativa y Banco Mundial : la educación comunitaria en Honduras - Tinoco, Marco Antonio, 1973- (Colección Códices., 2010)
Centers on the experience of the Proyecto Hondureño de Escuelas Comunitarias (PROHECO), located principally in rural areas, which began in 1999. It was originally funded by the World Bank but is now funded by the state.